Persentase Hasil Sosis Ayam Fermentasi Probiotik dengan Berbagai Bahan Aditif pada Tahap Fermentasi dan Tahap Pengeringan yang Berbeda - Roisu Eny Mudawaroch; Setiyono Setiyono; Lies Mira Yusiati; Edi Suryanto (Universitas Muhammadiyah Purworejo, 2018)
The purpose of this study was to determine the percentage yield of probiotic fermented chicken sausage with various additives at the fermentation and drying stages. The ingredients used were chicken meat and beef fat, salt, nitrite (NaNO2), sugar, pepper, garlic, sausage cartridges, BAL probiotic starter. The treatment in this study was fermented sausage with additives: nitrite, BAL Probiotics, and BAL Probiotics-nitrite. The parameters observed were the percentage yield of fermented chicken sausage at the fermentation and drying stages. The data obtained from the treatment were then analyzed for variance using a Split Plot Design. If there is a difference, continue with Duncan's New Multiple Range Test. The results of this study were the additives used had a very significant effect (P <0.01) on the percentage of probiotic fermented chicken sausage at the fermentation stage. The yield percentage of nitrite sausages is the highest when compared to BAL Probiotics and Probiotics-nitrite BAL sausages. Drying time at the fermentation stage had a very significant effect (P <0.01) on the yield of probiotic fermented chicken sausage. The longer the fermentation takes place, the lower the percentage of fermented sausage yields. At the drying stage, the additives used had a significant effect (P <0.01) on the yield of probiotic fermented chicken sausage. Drying time has a very significant effect on the percentage of probiotic fermented chicken sausage yield. The longer the fermentation takes place, the lower the percentage of fermented sausage yields. The conclusion of this study is that additives affect the growth of probiotic fermented chicken sausage during fermentation and drying. The longer the fermentation time and the drying time for probiotic fermented chicken sausage, the results of the probiotic fermented chicken sausage will decrease. The suggestion of this research is that there is a need for further research on other parameters in probiotic fermented chicken sausage.